2022
DOI: 10.1371/journal.pone.0268718
|View full text |Cite
|
Sign up to set email alerts
|

Associations between recreational cannabis legalization and cannabis-related emergency department visits by age, gender, and geographic status in Ontario, Canada: An interrupted time series study

Abstract: Legalization of recreational cannabis in Ontario included the legalization of flower and herbs (Phase 1, October 2018), and was followed by the deregulation of cannabis retailers and sales of edibles (Phase 2, February 2020). Research on the impact of cannabis legalization on acute care utilization is nascet; no research has investigated potential age, gender, and geographically vulnerable subgroup effects. Residents living in Northern Ontario not only have higher levels of substance use problems, but also hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…a sample of the population that has not been diagnosed with depression that is matched on key variables to individuals diagnosed with depression. We used (Kim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…a sample of the population that has not been diagnosed with depression that is matched on key variables to individuals diagnosed with depression. We used (Kim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study using ICD-10 codes from academic medical centers in Boston, Massachusetts (data from January 2012 to December 2019) found evidence of a gender difference; i.e., that legalization was associated with an increase in the ratio of women to men testing positive for cannabinoids upon ED presentation (122). Another study in the province of Ontario that considered gender found that cannabis legalization was associated with significant increases in cannabis-related ED visits, especially among women (123). Some further interesting trends emerged in this study.…”
Section: Cannabis-attributable Hospitalizationsmentioning
confidence: 99%
“…Some further interesting trends emerged in this study. For example, the initial legalization of cannabis use in October 2018 was associated with an increase in cannabis-related ED visits especially among women aged 45-64 years, whereas the legalization of cannabis edibles in 2020 was most strongly associated with increased cannabis-related ED visits among women aged 18-44 years (123). The authors proposed that the initial legalization effect was due to older adults (especially women) trying cannabis for the first time, whereas the effect of cannabis edible legalization may be related to the increased preference for edible products among younger adults (123).…”
Section: Cannabis-attributable Hospitalizationsmentioning
confidence: 99%
See 2 more Smart Citations